Trajetos cênicos do grupo parafolclórico da UFRN:que dança é essa? - Oliveira, Acacia Batista de (2011)
This paper aims at studying UFRN Parafolclórico Group, whose aesthetic formation is subjected to our analysis, specially at its two last performances, that is, Flor do Lírio (Lily Flower), 2004, and Debaixo do Barro do Chão (Under the Mud of the Ground), 2008. Three targets are envisaged here: to analyze the aesthetic ideas backing Parafolclórico Group exhibitions; to evaluate how their many folk elements interact with different artist languages in order to compose a certain choreography; and finally, to identify the aesthetic conformation placed behind the two different choreographs of the last performances, their trends and innermost features that differentiate them. In accordance with the Analysis of Contents (BARDIN, 2006), interviews have been made with the choreographers and the staff of the spectacles, resulting in elucidating answers to the understanding of their thematic axis. On the first chapter we called attention to motivating subjects as recollection, personal experiences, bibliography research, research in loco regarded as propelling forces of the creative works. Herein, folk culture is depicted as a dynamic process opening a frank dialogue with contemporary events and reinforcing their continuity. On the second chapter, we approached the aesthetic conformation and the scenic elements (costumes, light, scenario, make-up), integrating the studied spectacles and disseminating folk songs in various ways. As what concerns the subjects discourse, we have obtained support in authors like Robatto (1994); Lobo; Navas (2008); Burke (1989); Canclini (2006); Dufrenne (2005); Medeiros (2005); Pavis (2005); Silva (2005), among others. Those authors have provided us with an indispensable theoretic support which, added to the interviews, convinced us that the Parafolclórico Group s aesthetic conception tends to identify itself with the artist languages and other techniques of that Group. It also made sure that the Group s course aims at an aesthetic conception which is not limited to popular culture manifestations, like dance, but admits to play with other media in order to communicate its art. In view of this situation, we arrived to two conclusions: first: the group s interchanges emphasize the dynamic character of popular culture which, by establishing contacts with different realities, receives influences capable of extending its own continuity; second: the contemporary state of arts also improves multiple interchanges opening way, so, for many accomplishments in their field. Therefore, UFRN Parafolclórico Group inserts itself in the contemporary scenery by performing new evaluations of the popular dances as long as it puts them in contact with different technical, aesthetic, artist and culture combinations